2018
DOI: 10.7752/jpes.2018.02111
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Problem Statement: School physical education has been identified as an important time for increasing children's physical activity. Unfortunately, children are not as active and recommended. Pedometers and goal setting may be one way to increase physical activity. The purpose of the project was to evaluate the effectiveness of a pedometer-based goal-setting and encouragement intervention on physical activity in physical education. Participants totaled 200 (n = 94 control, n = 106 intervention) 3rd and 4th grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…According to the year of publication of the articles, it was found that it is the most recent literature that reports factors associated with the amount of physical activity in the physical education class. 2018 and 2020 were the years with the most articles included (21.4% each year) (Chase et al, 2018), (Tanaka et al, 2018), (Silva et al, 2018), (Jaitner et al, 2020), (Klaričić et al, 2020), (Howells et al, 2020).Following the years 2012, 2021 and 2023 (14.3% each year) (Moreno Z. et al, 2012), (Skala et al, 2012), (Wong et al, 2021), (Huertas-Delgado et al, 2021), (Llanos-Muñoz et al, 2023), (de Bruijn et al, 2023. And finally, the years 2016 and 2019 (7.1% each year), (Powell et al, 2016), (Gråstén et al, 2019).…”
Section: Results In Methodological Aspectsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the year of publication of the articles, it was found that it is the most recent literature that reports factors associated with the amount of physical activity in the physical education class. 2018 and 2020 were the years with the most articles included (21.4% each year) (Chase et al, 2018), (Tanaka et al, 2018), (Silva et al, 2018), (Jaitner et al, 2020), (Klaričić et al, 2020), (Howells et al, 2020).Following the years 2012, 2021 and 2023 (14.3% each year) (Moreno Z. et al, 2012), (Skala et al, 2012), (Wong et al, 2021), (Huertas-Delgado et al, 2021), (Llanos-Muñoz et al, 2023), (de Bruijn et al, 2023. And finally, the years 2016 and 2019 (7.1% each year), (Powell et al, 2016), (Gråstén et al, 2019).…”
Section: Results In Methodological Aspectsmentioning
confidence: 99%
“…Regarding the types of studies, most of the articles were quantitative. 71.4% of the articles reported a quantitative study type (Jaitner et al, 2020), (Klaričić et al, 2020), (Chase et al, 2018), (Wong et al, 2021), (Tanaka et al, 2018), (de Bruijn et al, 2023, (Huertas-Delgado et al, 2021), (Silva et al, 2018), (Gråstén et al, 2019), (Howells et al, 2020) tags. 21.4% were mixed studies (Powell et al, 2016), (Moreno Z. et al, 2012), (Skala et al, 2012).…”
Section: Results In Methodological Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sport is a systematic process in the form of all activities or efforts that can encourage, develop, and build the physical and spiritual potentials of a person as an individual or member of society in the form of games, competitions, and intensive physical activities to obtain recreation, development, and achievement [4] According to Chen, P et al (2020), one of the policy efforts in fighting pandemics is to increase endurance. "Stay at home" during the current period of lockdown or large-scale social restrictions should not stop society from doing physical activity and instead instill new creative ways of exercising and a more vital recognition of the importance of exercise [5] The general goals and objectives of the training include: improving general and comprehensive essential physical qualities, developing and enhancing specific physical potential, adding and refining techniques, developing and perfecting strategies, tactics, and playing patterns, and improving the quality of athletes' mental abilities [6] Some physical activity movements or exercises that can be done at home and their benefits, can be seen in table 1. According to Ganong (2001), the human body can fight all sorts of organisms or toxins that damage the body's tissues and organs.…”
Section: Introductionmentioning
confidence: 99%